Spatial Patterns of Origins and Destinations of Labor Emigrants: A Case Study of Bangladesh - Hossain, Shamim (Academia Journal of Humanities & Social Sciences, 2025)
Bangladesh is a densely populated country with limited natural resources and severe socio-economic disparities resulting in underemployment and unemployment. Consequently, many Bangladeshis seek overseas employment to improve their living standards. This study aims to identify the spatial patterns of labor emigrants' origins and destinations, providing insights into how the benefits of migration are distributed across the country. The research employs a quantitative methodology, analyzing data from 500 emigrants. The findings reveal that the benefits of labor migration are concentrated in a few districts, such as Comilla, Chittagong, Tangail, Chandpur, Dhaka, and Sylhet, while the majority of the country—especially the western regions—receives minimal benefit from remittances. The United Arab Emirates (UAE) is the top destination for Bangladeshi workers, followed by Oman and Saudi Arabia. On the other hand, the study also highlights that significant proportions of females migrated to the UAE (27%), Jordan (27%), Lebanon (20%), and Saudi Arabia (11%) between 2004 and 2016. The findings suggest a need for policies that distribute the benefits of labor migration more equitably and diversify labor markets beyond traditional destinations.